“More Important than COVID-19”: Temporary Visas and Compounding Vulnerabilities for Health and Well-Being from the COVID-19 Pandemic for Refugees and Asylum Seekers in Australia - Walsh, Moira; Due, Clemence; Ziersch, Anna (Refuge, 2022)
Refugees and asylum seekers on temporary visas typically experience interacting issues related to employment, financial precarity, and poor health and well-being. This research aimed to explore whether these issues were exacerbated by the social impacts of COVID-19. Interviews were conducted both prior to and during the COVID-19 pandemic with 15 refugees and asylum seekers living in South Australia on temporary visas. While this research found that COVID-19 did lead to a range of negative health and other outcomes such as employment challenges, a key finding was the reiteration of temporary visas as a primary pathway through which refugees and asylum seekers experience heightened precarity and the associated pervasive negative health and well-being outcomes. The findings emphasize the importance of immigration and welfare policy.